INVESTIGATIONS OF CHEMICAL PROCESSES OF O+ + H2 (V=0, J=0) REACTION USING THERMAL VARIATION IN THE IONOSPHERIC REGIONS - Yasar, Mehmet; Canyilmaz, Murat (Vinca Inst Nuclear Sci, 2018)
In this paper the chemical processes of the O+ + H-2 -> OH+ + H reactive reaction (exothermic) investigated with the thermal variation in the ionosphere by combining a gas kinetic theory model. Collision energy, reaction rate constant and total cross-sections as a function of ionospheric altitude and temperature are calculated. Also, all the other parameters related with the ionosphere are calculated for the 38.40 degrees N, 39.12 degrees E co-ordinates and year, day, and time taken as 2009, equinox and solstice, local time (12:00), respectively. It was found that the collision energy, reaction rate constant and cross-section values are decreasing with the increment of the ionospheric height and temperature. The total collision number takes the maximum values at lower ionosphere where the temperature is smallest and decreases with increasing height in upper ionosphere. The mean free path was found to close to each other and decay to zero nearly at 150 km for all months. It is estimated that the amount of energy which is released during the reaction can cause deterioration at the high level.
Keywords: ionosphere; chemical processes; exothermic reaction; gas kinetic theory